Elastic Displacement Spectrum-Based Design Approach for Buckling-Restrained Braced Frames. Issue 6 (17th August 2016) - Feng, Yulong; Wu, Jing; Meng, Shaoping
Abstract : The design focus for a buckling-restrained braced frame (BRBF) is that the buckling-restrained braces (BRBs) dissipate most of the seismic energy while the main frame retains a degree of elastic stiffness under a major earthquake. An elastic displacement spectrum based design method is presented in this article, which can directly determine the sectional area of the BRBs. The yield displacement in the roof of the main frame is taken as the target displacement under a major earthquake. An elastic displacement design spectrum is used to solve the target period of the BRBF. To validate this method, a six-story buckling-restrained braced steel frame is designed using the proposed method, and a series of nonlinear response history analyses (RHAs) are performed to verify the design result. The example shows that the required BRB area can be simply and accurately determined by the proposed method. The error between the given target displacement and the RHA results is 4.0% and 21.3% for BRBFs designed with BRB yield strength of 235 Mpa and 100 Mpa, respectively.